Mechanical Properties of Commercial Purity Aluminum Modified by Zirconium Micro-Additives - Ahmad Mostafa; Wail Adaileh; Alaa Awad; Adnan Kilani (Crystals, 2021)
The mechanical properties and the fractured surfaces of commercial purity aluminum modified by zirconium micro-additives were investigated by means of experimental examination. A commercial purity Al specimen was used as a reference material and seven Al-Zr alloys in the 0.02–0.14 wt.% Zr composition range (with 0.02 wt.% Zr step) were prepared by microalloying methods. Optical microscopy was used to examine the microstructures and to calculate the grain sizes of the prepared specimens. The phase assemblage diagrams were plotted and the relative amounts of solid phases were calculated at room temperature using FactSage thermochemical software and databases. Proof stress, strength coefficient and strain hardening exponent were measured from the stress-strain curves obtained from tensile experiments and Charpy impact energy was calculated for all specimens. The experiments showed that the grain size of commercial purity Al was reduced by adding any Zr concentration in the investigated composition range, which could be due to the nucleation of new grains at Al3Zr particle sites. Accordingly, the microhardness number, tensile properties and Charpy impact energy were improved, owing to the large grain-boundary areas resulted from the refining effect of Zr, which can limit the movement of dislocations in the refined samples. The basic fracture mode in all specimens was ductile, because Al has an FCC structure and remains ductile even at low temperatures. The ductile fractures took place in a transgranular manner as could be concluded from the fractured surface features, which include voids, ridges and cavitation.